Elemen-Elemen Lansekap Taman Ghairah dalam Bustanussalatin - Fakriah, Nurul; Fadhil, Muhammad Naufal (Jurnal Arsitektur Lansekap; Vol. 10, No. 2 Oktober 2024, 2024)
Bustanussalatin is a well-known work of Nuruddin Ar-Raniry, which contains detailed descriptions of a garden called Taman Ghairah. The manuscript was written in the seventeenth century in Aceh. This study aims to identify and enlist the landscape elements in Taman Ghairah, as mentioned in Bustanussalatin. The methods used in this study were content analysis of the copy of the Bustanussalatin manuscript and classified them according to the current knowledge of landscape architecture classification. The result shows that the landscape elements of Taman Ghairah, as written in Bustanussalatin, can be classified into soft elements, hard elements, and buildings. The findings of this research can be used as a reference for landscape design based on the history or locality in Aceh.